Congenital Candidiasis - Shwu-Meei Wang; Chyong-Hsin Hsu; Jui-Hsing Chang (Pediatrics and Neonatology)
Congenital candidiasis presents with a variety of clinical features. We report two neonates with congenital candidiasis characterized by diffuse erythematous papules associated with pneumonia and respiratory distress. Candida pseudohyphae were identifiable in skin scrapings. Systemic cultures were negative, but urine and sputum cultures grew Candida albicans. After prompt systemic antifungal therapy, the infants were discharged from hospital with no overt complications. This report highlights the presence of characteristic skin lesions associated with candidal infection, occurring within 24 hours of birth. This is an important observation which could help in the early diagnosis of congenital candidal infection.